Barthes’s Return to Michelet and the Question of New Life - Rushworth, Jennifer (Recherches sémiotiques / Semiotic Inquiry, 2019)
In this essay I investigate the role played by the nineteenth-century French historian Jules Michelet in the late lectures of Roland Barthes. While it is well known that one of Barthes’s first books was devoted to Michelet (1954), the presence of Michelet in the late works of Barthes has yet to receive due attention. This neglect is especially surprising, since Michelet is explicitly evoked repeatedly as a key model for Barthes’s elusive novelistic project, his so-called Vita Nova. Firstly, I undertake a reading of Barthes’s claims about Michelet’s vita n[u]ova in his late lectures and seminars. Secondly, I look at Michelet’s own use of the term vita n[u]ova, and propose that there is often a gap between Barthes’s Michelet and Michelet par lui-même. Thirdly, I reflect more broadly on the implications of these inconsistencies and discrepancies for the question of conversion which is at the heart of the concept of “new life”.